Validity, reliability, and responsiveness of daily monitoring visual analog scales in MASK-air (R) - Sousa-Pinto Bernardo; Eklund Patrik; Pfaar Oliver; Klimek Ludger; Zuberbier Torsten; Czarlewski Wienczyslawa; Bédard Annabelle; Bindslev-Jensen Carsten; Bedbrook Anna; Bosnic-Anticevich Sinthia; Brussino Luisa; Cardona Victoria; et al. (WILEY, 2022)
Background
MASK-air (R) is an app that supports allergic rhinitis patients in disease control. Users register daily allergy symptoms and their impact on activities using visual analog scales (VASs). We aimed to assess the concurrent validity, reliability, and responsiveness of these daily VASs.
Methods
Daily monitoring VAS data were assessed in MASK-air (R) users with allergic rhinitis. Concurrent validity was assessed by correlating daily VAS values with those of the EuroQol-5 Dimensions (EQ-5D) VAS, the Control of Allergic Rhinitis and Asthma Test (CARAT) score, and the Work Productivity and Activity Impairment Allergic Specific (WPAI-AS) Questionnaire (work and activity impairment scores). Intra-rater reliability was assessed in users providing multiple daily VASs within the same day. Test-retest reliability was tested in clinically stable users, as defined by the EQ-5D VAS, CARAT, or "VAS Work" (i.e., VAS assessing the impact of allergy on work). Responsiveness was determined in users with two consecutive measurements of EQ-5D-VAS or "VAS Work" indicating clinical change.
Results
A total of 17,780 MASK-air (R) users, with 317,176 VAS days, were assessed. Concurrent validity was moderate-high (Spearman correlation coefficient range: 0.437-0.716). Intra-rater reliability intraclass correlation coefficients (ICCs) ranged between 0.870 (VAS assessing global allergy symptoms) and 0.937 (VAS assessing allergy symptoms on sleep). Test-retest reliability ICCs ranged between 0.604 and 0.878-"VAS Work" and "VAS asthma" presented the highest ICCs. Moderate/large responsiveness effect sizes were observed-the sleep VAS was associated with lower responsiveness, while the global allergy symptoms VAS demonstrated higher responsiveness.
Conclusion
In MASK-air (R), daily monitoring VASs have high intra-rater reliability and moderate-high validity, reliability, and responsiveness, pointing to a reliable measure of symptom loads.